2018
DOI: 10.1042/bcj20180688
|View full text |Cite
|
Sign up to set email alerts
|

The oxidation of dehydroascorbic acid and 2,3-diketogulonate by distinct reactive oxygen species

Abstract: l-Ascorbate, dehydro-l-ascorbic acid (DHA), and 2,3-diketo-l-gulonate (DKG) can all quench reactive oxygen species (ROS) in plants and animals. The vitamin C oxidation products thereby formed are investigated here. DHA and DKG were incubated aerobically at pH 4.7 with peroxide (H2O2), ‘superoxide’ (a ∼50 : 50 mixture of and ), hydroxyl radicals (•OH, formed in Fenton mixtures), and illuminated riboflavin (generating singlet oxygen, 1O2). Products were monitored electrophoretically. DHA quenched H2O2 far more … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
63
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(66 citation statements)
references
References 92 publications
(116 reference statements)
2
63
0
1
Order By: Relevance
“…Proportion of the oxidised form of DHAA in tubers following thermal treatment, similarly to its proportion in raw tubers, was small and ranged from 1.2% (microwaving) to 2.7% (boiling). Literature shows, that depending on the conditions, ascorbic acid, besides being oxidised to the dehydro form (DHAA), may also undergo oxidative decomposition into oxalic acid and L-threonic acid [25]. Our results are comparable with the results of Jimenez et al [14].…”
Section: Rapidly Digestible Starch Slowly Digestible Starch Resistantsupporting
confidence: 90%
“…Proportion of the oxidised form of DHAA in tubers following thermal treatment, similarly to its proportion in raw tubers, was small and ranged from 1.2% (microwaving) to 2.7% (boiling). Literature shows, that depending on the conditions, ascorbic acid, besides being oxidised to the dehydro form (DHAA), may also undergo oxidative decomposition into oxalic acid and L-threonic acid [25]. Our results are comparable with the results of Jimenez et al [14].…”
Section: Rapidly Digestible Starch Slowly Digestible Starch Resistantsupporting
confidence: 90%
“…All three forms have been shown to have antioxidant properties. 76 It was also suggested that the catabolism of ascorbic acid correlates with the rate of cell expansion, 77 and that the metabolites of 2,3-diketo-L-gulonate play a role in pathogen defense. 78 Date palm seedlings treated with silicon and grown under control conditions also accumulated plant biotic defense metabolites such as the antifungal aromatic anofinic acid, 79 the broad-spectrum antifungal agent glucoraphanin 80 and the jasmonic acid derivative epi-4ʹ-hydroxyjasmonic acid.…”
Section: Discussionmentioning
confidence: 99%
“…In the apoplast, reduced AA concentration is lower while the oxidized form of AA, dehydroascorbate (DHA), is more predominant than in the symplast (Smirnoff and Arnaud, 2019). The breakdown of DHA results in the formation of derivatives, such as oxalic, threonic acid and 2,3-L-diketogulonate in the apoplast (Dewhirst and Fry, 2018), which leads to generation of H 2 O 2 that could play a role in defense signaling (Smirnoff, 2018). AO was shown to play a role in cell growth (De Tullio et al, 2013) and work on transgenic AO overexpression lines demonstrated that AO plays a role in stress tolerance (Yamamoto et al, 2005;Pignocchi et al, 2006;Garchery et al, 2013;Karpinska et al, 2018).…”
Section: Introductionmentioning
confidence: 99%